2011
DOI: 10.1038/mi.2011.9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular signatures of a disturbed nasal barrier function in the primary tissue of Wegener's granulomatosis

Abstract: Wegener's granulomatosis (WG) is a complex autoimmune disease of unknown etiology, frequently involving localized inflammation of the nasal mucosa as an early manifestation. The current hypothesis suggests that the disease is triggered by a disturbed interaction between genetic and environmental effects, such as an altered microflora at mucosal layers. In this study, a systematic assessment of 49 transcripts with potential pathophysiological relevance was performed using quantitative real-time PCR in nasal muc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 50 publications
1
18
1
3
Order By: Relevance
“…A previous study has shown that expression of NLRC3 is down-regulated in patients with the autoimmune disease Wegener’s granulomatosis 24 . Moreover, a loss-of-function mutation in the gene encoding the NLRC3-like protein in zebrafish results in systemic inflammation 25 .…”
mentioning
confidence: 96%
“…A previous study has shown that expression of NLRC3 is down-regulated in patients with the autoimmune disease Wegener’s granulomatosis 24 . Moreover, a loss-of-function mutation in the gene encoding the NLRC3-like protein in zebrafish results in systemic inflammation 25 .…”
mentioning
confidence: 96%
“…Analysis of the TaqMan low-density array real-time PCR including cluster analysis was performed as described recently. 18 …”
Section: Statisticsmentioning
confidence: 99%
“…18 A complete list of the genes analyzed and respective real-time PCR assays used in this study are provided in Supplementary Table S1.…”
Section: Taqman Low-density Arraysmentioning
confidence: 99%
“…In contrast, therapeutic regimens in rheumatic or lymphatic conditions are based on immuno-, chemo-and radiotherapy [4,5]. Surgical approaches are restricted to histologically evidenced cases to provide immunological trigger effects with a subsequent disease aggravation [6][7][8]. In addition, corticosteroids, a considerable component of anti-inflammatory treatment of orbital complications in acute rhinosinusitis, can mask lymphatic or rheumatic conditions and prolong time to diagnosis dramatically [9].…”
Section: Introductionmentioning
confidence: 98%